PENGEMBANGAN KOMIK FANTASI BERTEMA PAHLAWANKU SEBAGAI MEDIA PEMBELAJARAN IPS DI KELAS IV SEKOLAH DASAR - Mohamad Rizki; Zerri Rahman Hakim; Ana Nurhasanah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the development of my hero-themed fantasy comic as a social science learning media for fourth-grade students in elementary school and the level of feasibility of the comic and students' responses to the comic developed. The study described in this article used a research and development method (RnD) with the research design of the Borg and Gall model modified by Sugiyono. There were 6 stages of development in the study, namely problem analysis, data collection, product design, design validation, design revision, and product testing (limited). The instruments in the study were the form of expert validation sheets and students’ response questionnaires. This comic was validated by 2 media experts, 2 material experts, and 2 linguists and tested on 26 fourth-grade students at SDN Pasirmae 1. The results of the study were the development of my hero-themed fantasy comic as social science learning media for fourth-grade students in elementary school. The feasibility of the comic based on expert validation was an assessment in the very feasible category with a percentage of 83.88% from media experts, 81.66% from material experts, and 90% from linguists. Meanwhile, the assessment of the student responses showed a percentage of 95.32% which was included in the very good category.